Determinants of migrant workers remittances: a case study of the Gulf Cooperation Council countries - Alnuaimi, Ahmed Abdulla Rashed (2021)
The purpose of this study is to analyze macroeconomic, non-macroeconomic and financial sector development (FSD) factors that influence migrant workers remittances in the selected Gulf Cooperation Council (GCC) countries. An augmentedgravity model was employed as the theoretical framework and econometric methods were used to examine the relationships between macroeconomics (Gross Domestic Product (GDP), exchange rates, and inflation rates), non-macroeconomics (borders, cultural and history, partner countries, distances, and language) and FSD factors(credit to private sector (CPS) and openness to trade (OT)) towards remittances. Data sources fromWorld Bank and group of central banks from 1989 to 2012 wereutilized. The empirical findings demonstrated that the GDP of the countries was the most significant factor in influencing the remittance flows. Moreover, other macroeconomic factors were also found to be significant in affecting the remittances including exchange and inflation rate. The result further suggested that, the GCC countries share similar results for the following non-macroeconomic factors language,cultural and history do provide the opportunity to remit extensively. The results also suggested that the development factors in financial sector including CPS and OT were significant and positively associated to remittances. In conclusion, the GDP (9.421, p<0.001) which is known as macroeconomic factor was found to be the significant in determining migrant workers remittances in the selected GCC countries, followed by distance (7.101, p<0.001) for non-macroeconomic and CPS (1.449, p<0.001) under FSD factor. The implication of the study suggested that GCC governments need to understand the consequences of the outflow remittances and were recommended to identify significant factors that shape the size of remittance flows. Both regions were proposed to formulate policy systems of informal channels, including addressing the weaknesses of the formal systems.